Case Report: Cutaneous Squamous Cell Carcinoma Arising From the Ulcer of the Lesions of Dupuytren’s Disease on the Palm - Sun, Qingmiao; Fu, Bin; Li, Sheng; Fang, Hong; Qiao, Jianjun (Frontiers in Oncology, 2021)
Dupuytren’s disease is a benign fibromatosis that mainly involves the fascia of the palm and digits. The relationship between Dupuytren’s disease and the evolution of cutaneous squamous cell carcinoma is still unclear. Here we report the case of a 52-year-old female with squamous cell carcinoma arising from the ulcer of the lesions of Dupuytren’s disease on the left palm. To our knowledge, this is the first reported case in the English literature of squamous cell carcinoma on the palm of someone with Dupuytren’s disease.